Nitrogen Fertilization of Lawns Enhanced Soil Nitrous Oxide Emissions by Increasing Autotrophic Nitrification - Xun, Zhifeng; Xu, Tianyue; Ren, Baihui; Zhao, Xinghan; Quan, Zhi; Bai, Long; Fang, Yunting (Frontiers in Environmental Science, 2022)
As nitrous oxide (N2O) is one of the most important greenhouse gases, N2O emission pathways and regulation techniques in soils with different vegetation types have become a research focus. Currently, a diverse array of research exists on the N2O emissions from soils of different vegetation types, e.g., forest, grassland, and agriculture. Few studies have investigated the microbial processes of N2O emissions from lawn soils. Fertilization levels in lawn soils are often similar to or much higher than those in agricultural ecosystems, thus fertilized lawn is an important source of atmospheric N2O. In the study, we employed the 15N-nitrate labelling method combined with the nitrification inhibition technique to distinguish microbial processes and their contribution to N2O emissions in long-term nitrogen fertilised lawns. We found that the N2O emission rate from the control treatment was 1.0 nmol g-1 h-1 over the incubation, with autotrophic nitrification contributing 60%. The N2O emission rate increased to 1.4 nmol g-1 h-1 from the soil treated with long-term N fertilization, and the contribution of autotrophic nitrification increased to 69%. N fertilization did not significantly increase the contribution of denitrification (24–26%) in the total N2O emissions. However, N fertilization substantially decreased the contribution of heterotrophic nitrification from 13% to 0.4% in the total N2O emissions. Co-denitrification to N2O was detected but the overall contribution was of minor importance (3–5%). The correlation analysis revealed that soil NO3- levels were the main influencing factors in the N2O producing microbial processes. Our results suggest that N fertilization altered both N2O production rates and the contribution pattern of microbial processes, and indicate the autotrophic nitrification and heterotrophic nitrification are more sensitive to N fertilization than denitrification and co-denitrification.